ZnO Nanocomposite Membranes for Desalination - Vijesh, A. M.; Liya, J.; Shyma, P. C. (Journal of Applied Membrane Science & Technology, 2017)
Severe drinking water scarcity is a major problem around the world and pressure driven membrane processes are gaining importance in the field of water purification. This work mainly focuses on improving membrane performance in terms of hydrophilicity, solute rejection, etc. It emphasizes on the preparation of polysulfone (PSf) based blend membranes via phase inversion method. PSf membrane is modified by the addition of zinc oxide (ZnO) nanoparticle at various compositions and the resultant membrane performances were studied. The PSf-ZnO membranes were characterized by ATR-IR and SEM. These membranes showed much better salt rejection performance.Â 